2023
DOI: 10.32604/ijmhp.2022.025546
|View full text |Cite
|
Sign up to set email alerts
|

Research on Career Identity in China: A Literature Review

Abstract: Career identity is one of the important topics to study the psychological problems of employees, especially after the outbreak of CoV-19. Being a populous country in the world, China has a large number of employees from all walks of life, and its research on career identity has attracted more and more attention. Thus, this study aims to sort out the history, characteristics, and trends of the research on career identity in China through a literature review, which can help more scholars pay attention to China's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
1
1
Order By: Relevance
“…Also, Clemans and Yeong (2020) (19) found the majority of staff nurses had a high perception level regarding professional identity. On the opposite, the result of the present study is contradicted with the result of a study conducted by Liu WH and Zhao (2023) (20) who revealed that nurses perceived their level of professional identity to be above average. Moreover, Tomlinson et al (2021).…”
Section: Discussioncontrasting
confidence: 99%
“…Also, Clemans and Yeong (2020) (19) found the majority of staff nurses had a high perception level regarding professional identity. On the opposite, the result of the present study is contradicted with the result of a study conducted by Liu WH and Zhao (2023) (20) who revealed that nurses perceived their level of professional identity to be above average. Moreover, Tomlinson et al (2021).…”
Section: Discussioncontrasting
confidence: 99%
“…A similar mediating relationship has been shown in a study by Dobrow and his colleagues wherein he found that that people with a stronger sense of calling in their careers were more likely to report higher levels of job satisfaction and engagement ( Hall and Chandler, 2005 ; Yap et al, 2010 ; Duffy et al, 2012 ). Hence, when people are motivated internally, as opposed to externally, they work with greater interest, excitement, and confidence, and when they engage in self-motivated behavior, their vitality, self-esteem, and overall wellbeing may increase ( Ryan and Deci, 2000 ; Steger and Dik, 2009 ; Chen et al, 2023 ; Ou and Gu, 2024 ).…”
Section: Discussionmentioning
confidence: 99%